ANALISIS PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN RISIKO KEUANGAN DALAM INTERIM REPORT - Devi Febina Christie; Marsono Marsono (Diponegoro Journal of Accounting, 2014)
This research aims to get empirical proof about the factors which are influence financial risk disclosure in interim reports of manufacture firms. Corporate characteristic used in this research are board size, board composition, audit committee size, concentration of ownership, profitability, leverage, and financial reporting risk. This research uses purposive sampling to carry out sample selection. There are 105 interim financial reports from manufacture firms which are listed in BEI (Bursa Efek Indonesia) period of June 30 from 2011 until 2013 become the sample in this research. Agency theory and Stakeholder theory are used to explain relationship inter variable. Statistic method that used for examining the hypothesis is multiple regression analysis. The result of this research showed that profitability and leverage degree are positive related significant with corporate risk disclosure. Concentration of ownership is negatively significant with corporate risk disclosure, while board size board composition, audit committee size, and financial reporting risk are not significant with corporate risk disclosure.